Introduction of cryIB-cryIAa Hybrid Gene Into Rice (Oryza sativa) Genom cv. Rojolele using Agrobacterium-Mediated Transformation - SYAMSIDAH RAHMAWAT; INEZ HORTENSE SLAMET-LOEDIN (HAYATI Journal of Biosciences, 2006)
Rojolele is one of Indonesian local variety from Javanica group that susceptible to yellow stem borer (Scirpophaga incertulas). Previous study showed that Rojolele can be cultured and regenerated in vitro. Two cry genes, cryIB-cryIAa were fused and introduced into rice cv. Rojolele in an attempt to improve resistance and to obtain durable resistance rice against the yellow stem borer. Two-week old embryogenic calli of Rojolele rice were inoculated with Agrobacterium tumefaciens harbored with binary vector pCAMBIA 1301, 1303, or 1304 carrying cryIB-cryIAa hybrid gene, hygromycin resistant gene (hpt), and -glucuronidase (gus) gene interrupted with an intron. The transformed calli were selected gradually on medium containing hygromycin (50, 100 mg/l) and regenerated on medium containing 0.5 mg/l IAA and 0.3 mg/l BAP. GUS activity in infected calli was detected by histochemical assay 3 days after inoculation. The highest (100%) transformation efficiency were obtained from calli transformed with pCAMBIA 1303 and 1304. Thirty four out of 77 transformed shoots were tested positive for the cryIB-cryIAa gene using PCR analysis. These shoots were grown in the soil to maturity and to collect the seeds. PCR analysis of the T1 progeny revealed that two out of six lines tested showed a Mendelian segregation pattern. These two lines were also potentially resistant to yellow stem borer based on bioassay in planta. Key words: cryIB-cryIAa hybrid gene, yellow stem borer